Evaluation of commercially available on-line analyzers for measurement of natural gas contaminants - Zineddin, Khalid Mohamad, author; Olsen, Daniel, advisor; Jathar, Shantanu, committee member; Carlson, Kenneth, committee member (Colorado State University. Libraries, 2021)
The proliferation of natural gas usage and extraction has led to never-before-seen levels of demand across the United States in several industries. Because of this increased demand for quality processed natural gas, a need has arisen to streamline its processing and distribution for faster and more efficient delivery to customers. One method to achieve this is by consolidating natural gas contaminant analyzers at processing and distribution sites; current sites typically operate with multiple separate gas analyzers, each dedicated to measuring one individual contaminant species. Recent developments in laser-based gas composition analysis (in particular Tunable Diode Laser Absorption Spectroscopy or TDLAS) as well as advances in gas chromatograph (GC) technology have given rise to commercially-available analyzing instruments which are capable of detecting and measuring multiple gas contaminants simultaneously. In order to verify the effectiveness and reliability of these new technologies, three specific gas analyzing instruments (herein referred to as Instruments A, B, and C) were selected for in-depth laboratory and field testing. The main objective of this research is to quantify the accuracy, precision and uncertainty of these new multi-species gas analyzers and compare their performance with existing gas analyzers currently in use by natural gas processing and distribution organizations. Four natural gas contaminant species were specified for evaluation of the natural gas contaminant analyzers; these are water (H2O), hydrogen sulfide (H2S), oxygen (O2) and carbon dioxide (CO2). Laboratory testing was performed first by sampling existing natural gas from three separate sources then by custom gas mixtures blended in-house from pure component gases to simulate four levels of contaminants (Low, two Mid-range blends, and High). For results verification a sample of each gas mixture (both source natural gas and custom blends) was submitted to EMPACT Analytical Inc. for composition analysis. Following laboratory testing, two instruments were selected for ongoing (through February 2022) field testing to simulate "real-world" conditions and their results are compared with those of existing on-site gas contaminant analyzers. It was concluded that Instrument A (TDLAS-based) was the most accurate and reliable of the three analyzers under test and required the least amount of user intervention to maintain satisfactory operation. Instrument B (also TDLAS-based) ranked a close second-place, having slightly less accuracy than Instrument A in measuring gas concentrations and falling short by its inability to detect O2; it also experienced multiple failures which required user intervention and/or shipping the instrument back to the manufacturer for repair and reconfiguration. Instrument C (GC-based) performed the poorest of the three analyzers with very low accuracy in measuring O2 and H2O to the point of being essentially non-detected species; it also required in-depth user intervention for initial setup and on multiple occasions during operation which was determined to be inappropriate for the intended application.
Keywords: gas mixture; natural gas; measurement; gas analyzer